FORENSIC AND PSYCHOLOGICAL EXAMINATION IN REGARD TO MINORS WITHIN CRIMINAL CASES (Law and Safety, 2018)
The article is focused on the issues of conducting forensic and psychological examination in regard to minors within criminal cases. The following issues have been revealed: the possibility of participation of a psychologist in the investigation of criminal cases concerning minors; requirements for the appointment of a forensic and psychological examination in regard to minors; cases of its compulsory conduction; substantive types of psychological examinations carried out in relation to minors within criminal cases; tasks solved by an expert psychologist during the mentioned examinations; the limits of the competence of the expert psychologist and the informative content of the criminal cases, which should be submitted to the expert’s research.The main emphasis was placed on the peculiarities of forensic and psychological examination of minors – victims in cases of sexual offenses and in cases brought about by the failure of parents to fulfill their duties, which led to grave consequences. The main approaches to solving psychological issues that arise in practice have been stated.It has been stressed that the ability of the victim to understand the nature of the actions against him and actions of the offender involves sufficient formation of the level of mental development, awareness of sexual relations between a man and a woman, the ability to distinguish the elements of sexual nature in the behavior of the opposite sex, to assess the criminal nature of the situation, to recognize real intentions of the offender, to assess the perspectives and possible consequences of the situation.Forensic and psychological examination is one of the means of establishing the truth in the proceedings and a source of evidence in the case. While investigating criminal cases by the results of a forensic and psychological examination concerning minors, answers to the raised questions are provided on the basis of the analysis of the criminal case files and the establishment of peculiarities of the mental activity of minors that are essential for a criminal case.
Keywords: forensic and psychological examination, substantive types, minors, individual and psychological features, ability of minors.